"All that glitters is not gold". Issue 6 (11th October 2021) - Mohanan Nair, Krishna Kumar; Namboodiri, Narayanan; Valaparambil, Ajitkumar
Abstract : A 63‐year‐old gentleman presented to the emergency room (ER) with complaints of sudden onset of palpitation for the last 1 hour. He denied any presyncope or syncope. He was tachycardic with pulse rate of 120 beats per minute. His blood pressure was 110/70 mm Hg. A 12‐lead electrocardiogram (ECG) was taken. What is the likely diagnosis?